Peranan Badan Usaha Milik Desa (BUMDes) dalam Perekonomian Masyarakat Desa Kabupaten Aceh Besar - Putri Rauzati; Irfan Zikri; Ahmad Humam Hamid (Jurnal Ilmiah Mahasiswa Pertanian, 2022)
BUMDes is a village business formed/established by the village government where capital ownership and management are carried out by the village government and the community. The purpose of the establishment of BUMDes is the government's effort to improve the financial capacity of the village government in administering government and increasing community income through various economic business activities of rural communities. The purpose of this study was to find out how the role of Village Owned Enterprises (BUMDes) in the economy of the community in Aceh Besar District. The locations used as research sites are Blang Krueng Village, Lambro Deyah Village and Meunasah Krueng Village, Aceh Besar District. The location selection is done by (purposive sampling). Purposive Sampling is the determination of the sample with certain considerations such as considering that the respondent is involved in BUMDes activities. The analytical method used in this study is a quantitative descriptive method. The results of this study can be concluded that the existence of BUMDes has an influence on rural communities, where the previous mean income value is 1.85, namely income category 1 which is 0 – 1,000,000 and category 2 is 1,000,000 – 2,000,000. The mean value of the respondent's income after joining has changed to 2.78, which is in category 3 which is 2,000,000 – 3,000,000 and category 4 is 3,000,000. The results of this study can be concluded that the existence of BUMDes has an influence on rural communities, where the previous mean income value is 1.85, namely income category 1 which is 0 – 1,000,000 and category 2 is 1,000,000 – 2,000,000. The mean value of the respondent's income after joining has changed to 2.78, which is in category 3 which is 2,000,000 – 3,000,000 and category 4 is 3,000,000. The results of this study can be concluded that the existence of BUMDes has an influence on rural communities, where the previous mean income value is 1.85, namely income category 1 which is 0 – 1,000,000 and category 2 is 1,000,000 – 2,000,000. The mean value of the respondent's income after joining has changed to 2.78, which is in category 3 which is 2,000,000 – 3,000,000 and category 4 is 3,000,000.Income leveltan community economyt the village before and after the existence of BUMDes there was a displacement, meaning that bumdes plays a role inincome transfertan community economyt. Before joining BUMDes, the income was on the low criteria as many as 30 people, after joining 4 people. On the criteria of moderate income before joining as many as 18 people after joining to 25 people. On the high income criteria before joining there were 14 people after joining 17 people. On very high income criteria before joining 3 people after joining 17 people. Keywords:  BUMDes, Economy, Income.